2006
DOI: 10.1300/j096v11n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Training Methods and Association with Worker Injury on Colorado Dairies

Abstract: The goals of this study were to define the current methods for training entry-level workers on Colorado dairies, to measure the relationship of training methods to the incidence of work-related injuries on those operations, and to characterize the nature and cause of injuries reported by participating workers. Seventy-two workers from 15 dairies from Weld, Morgan, Larimer and Yuma counties volunteered to be interviewed privately in the language of their choice. Training methods were classified by content (task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
4
26
0
Order By: Relevance
“…When safety information is viewed as meaningful, valuable, and relevant to everyday experiences, it may enhance motivation to learn and aid with memorization and recollection processes (63). One way to ensure OSH training reflects workplace realities is to integrate it with task training as much as possible (13). Whether delivered separately or in conjunction with task training, careful attention should be made to acknowledge what is feasible or realistic for the workers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When safety information is viewed as meaningful, valuable, and relevant to everyday experiences, it may enhance motivation to learn and aid with memorization and recollection processes (63). One way to ensure OSH training reflects workplace realities is to integrate it with task training as much as possible (13). Whether delivered separately or in conjunction with task training, careful attention should be made to acknowledge what is feasible or realistic for the workers.…”
Section: Resultsmentioning
confidence: 99%
“…Román-Muñiz et al (13) found that training provided by coworkers had a protective effect against work-related injuries, but this effect was not found when provided by dairy managers. They speculated that coworkers may be better able to deliver safety information in an informal and culturally acceptable manner, compared to managers who may have inadequate Spanish language skills and/or a limited comprehension of the cultural factors that influence effective communication (p. 23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human-to-cattle spread of M. bovis is more likely to occur on dairy operations in which human/animal contact is frequent and a large part of the workforce is Hispanic [7][8][9]. In one study of 165 human M. bovis cases from 1995 to 2005, Hispanics, relative to non-Hispanics, had 10 times the odds of having M. bovis than M. tuberculosis [10].…”
Section: Discussionmentioning
confidence: 99%